2012
DOI: 10.7314/apjcp.2012.13.6.2459
|View full text |Cite
|
Sign up to set email alerts
|

Residential Radon and Lung Cancer Risk: An Updated Meta-analysis of Case-control Studies

Abstract: Background: Numbers of epidemiological studies assessing residential radon exposure and risk of lung cancer have yielded inconsistent results. Methods: We therefore performed a meta-analysis of relevant published casecontrol studies searched in the PubMed database through July 2011 to examine the association. The combined odds ratio (OR) were calculated using fixed-or random-effects models. Subgroup and dose-response analyses were also performed. Results: We identified 22 case-control studies of residential ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 41 publications
1
27
0
2
Order By: Relevance
“…' We respectfully disagree. While our paper is not an original epidemiological study on the association between lung cancer and low-level radon in Swedish dwellings, such studies have been performed [1] and show results completely compatible with the results of previous multicenter studies or meta-analyses in Europe and the USA [2][3][4] and large studies from China [5]. In our study we used the exposure-response (ER) function found by Darby et al [2], since the European results were considered most representative of the Swedish situation.…”
supporting
confidence: 49%
“…' We respectfully disagree. While our paper is not an original epidemiological study on the association between lung cancer and low-level radon in Swedish dwellings, such studies have been performed [1] and show results completely compatible with the results of previous multicenter studies or meta-analyses in Europe and the USA [2][3][4] and large studies from China [5]. In our study we used the exposure-response (ER) function found by Darby et al [2], since the European results were considered most representative of the Swedish situation.…”
supporting
confidence: 49%
“…Exposure to radon gas is the second-leading cause of lung cancer (behind tobacco), and the leading cause in non-smokers. 1 Several case-control studies report an 8-12% increase in lifetime risk of lung cancer associated with each 100 Becquerel per cubic metre (Bq/m 3 ) increase in long-term exposure to radon, [2][3][4] and no evidence of a threshold or "safe" level of exposure. 2 Smoking and radon also interact synergistically, causing a greater increase in lung cancer risk for smokers than for nonsmokers.…”
mentioning
confidence: 99%
“…Similar studies from other countries have reported similar results, therefore much of the evidence for residential radon policy in Canada and worldwide has been derived from meta-analyses that increase statistical power by combining data from multiple case-control studies. [2][3][4] Ecologic designs provide another way to increase the size of study populations. To date there have been no ecologic studies on radon exposure in Canada, but those conducted elsewhere report associations between radon and multiple cancers.…”
mentioning
confidence: 99%
“…Residential radon exposure is considered a risk factor for lung cancer ( [1,2] and others) but there is a lot of controversy on this topic; some authors suggest that it is only an assumption [3,4]. On the other hand, a short-term radon exposure can be healthy from the balneological point of view, as we know from many spas around the world [5,6].…”
Section: Introductionmentioning
confidence: 99%